2021
DOI: 10.1002/celc.202100446
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Immunomagnetic Ochratoxin A Sensing: Steps Forward in the Application of 3,3’,5,5’‐Tetramethylbenzidine in Amperometric Assays

Abstract: Electrochemical methods offer great promise in meeting the demand for user-friendly on-site devices for monitoring important parameters. The food industry often runs own lab procedures, for example, for mycotoxin analysis, but it is a major goal to simplify analysis, linking analytical methods with smart technologies. Enzyme-linked immunosorbent assays, with photometric detection of 3,3',5,5'-tetramethylbenzidine (TMB), form a good basis for sensitive detection. To provide a straightforward approach for the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Previous studies of ours have shown that a flow cell combined with an SPE consisting of a gold working electrode, a platinum counter electrode and a silver pseudo-reference electrode buffered at pH 1, showed stable and reproducible responses over several measurement cycles for HRP/H 2 O 2 /TMB immunoassays. 14 However, this macroscopic flow cell required rather high sample volumes and increased flow rates that consumed a lot of reagents. We therefore focused on integrating a more economical system organised around a microfluidic flow cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of ours have shown that a flow cell combined with an SPE consisting of a gold working electrode, a platinum counter electrode and a silver pseudo-reference electrode buffered at pH 1, showed stable and reproducible responses over several measurement cycles for HRP/H 2 O 2 /TMB immunoassays. 14 However, this macroscopic flow cell required rather high sample volumes and increased flow rates that consumed a lot of reagents. We therefore focused on integrating a more economical system organised around a microfluidic flow cell.…”
Section: Resultsmentioning
confidence: 99%
“…TMB is oxidised by HRP with hydrogen peroxide as a cosubstrate to the corresponding diimine and can be detected optically by absorbance measurement at 450 nm with a spectrophotometer or plate reader; or electrochemically by potentiometric or amperometric methods via reduction to the original form. 14,15 The second method is usually chosen for sensor development, as it allows measurements with high sensitivity at lower instrumental cost, enabling miniaturisation along the way. 16 Indeed, the availability of miniature potentiostats and screen-printed electrodes (SPE) provides an ideal basis for the transition from conventional immunoassays to integrated immunosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of the magnetic beads into a lateral flow system appears feasible as well and represents another future application of our magnetic beads. As shown previously, changing the detection mode from optical to electrochemical detection is also possible which allows for further miniaturization of the system and mobile testing [ 49 ]. Beyond that, the use of magnetic beads will also enable automation and implementation of the assay into autonomous sensors for possible on-site analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Poly­(methyl methacrylate) (PMMA) was used as a substrate to design the flow cell. The procedure for developing the SPGE-integrated miniaturized platform is explained in the Supporting Information (Figure S1), and more details of the fabrication procedure can be obtained from previous work …”
Section: Introductionmentioning
confidence: 99%